Sensory analysis of canned small tilapia with non-commercial sizes (Research, Society and Development, 2023)
In the food sector, sensory analysis has great importance for evaluating the acceptability by consumers and will also evaluate the quality of a product to be tested. This work aims to perform sensory analysis of canned products of different sizes of Nile tilapia (Oreochromis niloticus) to stimulate the consumption of canned fish. Attribute profile tests were applied, evaluating appearance, color, aroma, flavor, and texture, the judge was asked to evaluate the attributes specified on the card after tasting the samples, using a 9-point verbal and numerical scale. To evaluate the effect of size on sensory characteristics the Friedman test was used. Considering the significance level of 5%. In case of a statistically significant effect, the Conover test was used. Spearman correlation coefficients were also computed for these variables. Sensory characteristics showed strong positive correction between color/appearance, taste/purchase intention, overall evaluation/purchase intention, overall evaluation/taste, and overall evaluation/consistency. The appearance of the products correlated with their coloration, indicating that when they tasted the canned tilapia in the different sizes, they were accepted, because the product presented good characteristics in these two variables. It is concluded that small, i.e., out of commercial size tilapia that were canned, proved to be effective in producing canned fish for marketing, which may impact aquaculture production.